2002
DOI: 10.1063/1.1499497
|View full text |Cite
|
Sign up to set email alerts
|

Effective screened potentials of strongly coupled semiclassical plasma

Abstract: Abstract. The pseudopotentials of particle interaction of a strongly coupled semiclassical plasma, taking into account both quantum-mechanical effects of diffraction at short distances and also screening field effects at large distances are obtained. The limiting cases of potentials are considered.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
87
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(89 citation statements)
references
References 12 publications
1
87
0
1
Order By: Relevance
“…In [41] with the help of linear response method an effective potential was obtained, which is also used in this paper, by taking in to account both the diffraction effects at short distances and the screening effect at large distances…”
Section: Microfield Distribution Functionmentioning
confidence: 99%
“…In [41] with the help of linear response method an effective potential was obtained, which is also used in this paper, by taking in to account both the diffraction effects at short distances and the screening effect at large distances…”
Section: Microfield Distribution Functionmentioning
confidence: 99%
“…In addition, it has been shown that the interaction potential in strongly coupled semiclassical plasmas would not be represented by the conventional DebyeHückel model because of nonideal particle interactions due to collective and quantum effects. [10][11][12][13] However, the behavior of the Wannier threshold law for the double-electron escape in strongly coupled semiclassical plasmas has not been specifically investigated as yet. Thus, in this brief communication we investigate the quantum and plasma screening effects on the Wannier threshold law for the double-electron escape from the ion in strongly coupled semiclassical plasmas.…”
mentioning
confidence: 99%
“…Thus, in this brief communication we investigate the quantum and plasma screening effects on the Wannier threshold law for the double-electron escape from the ion in strongly coupled semiclassical plasmas. The screened renormalized electron is obtained by using the screened pseudopotential model, 10 taking into account the quantum and correlation effects as a function of the de Broglie wavelength, Debye length, and charge of the residual ion. Furthermore, the quantum and plasma screening effects on the Wannier exponent for the double-electron escape is obtained by considering the screened effective charge of the residual ion in strongly coupled semiclassical plasmas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This velocity dependence of the plasma screening length r 0 (v) is readily understood since the dynamic plasma screening effect turns out to be the static plasma screening case such as r 0 (v) → r D when the velocity of the projectile electron is smaller than the electron thermal velocity. In addition, an accurate form of the screened effective pseudopotential [4] of the particle interactions in strongly coupled semiclassical plasmas taking into account both the quantum-mechanical and plasma screening effects was obtained on the basis of the dielectric response function analysis. Hence, the velocity dependent dynamic interaction potential V Dy (r, v) between the projectile electron and target ion with nuclear charge Ze in strongly coupled semiclassical plasmas based on the Ramazanov-Dzhumagulova model [4] with the dynamic screening length r 0 (v) is obtained by…”
mentioning
confidence: 99%